Zakat Management of Lazismu Purworejo: Total Quality Management Approach - Iyus Herdiana Saputra; Rofiq Nurhadi; Hans-Christian Günther (Cakrawala: Jurnal Studi Islam, 2023)
This study aimed to explore the planning, organization, implementation, and supervision processes of Lazismu Purworejo and to assess its management through the lens of Total Quality Management (TQM). Employing a descriptive qualitative approach, the study involved administrators, managers, beneficiaries (mustahik), and users as subjects. The findings revealed that Lazismu Purworejo underwent a quality audit by the Central Lazismu, achieving commendable results and obtaining an Unqualified Opinion (WTP), categorizing it as “green.” The application of TQM principles in management was evident in the satisfactory service levels for customers, improvements in operational processes, and the collective and collegial involvement of leadership in Lazismu Purworejo. This collaborative approach contributed to the establishment of a robust obligatory system for zakat management.